The Effect of Oxycodone on Post-operative Pain and Inflammatory Cytokine Release in Elderly Patients Undergoing Laparoscopic Gastrectomy - Lao, Wei-long; Song, Qi-liang; Jiang, Zong-ming; Chen, Wen-di; Zheng, Xian-he; Chen, Zhong-hua (Frontiers in Medicine, 2021)
Background To evaluate the effect of oxycodone on postoperative pain and inflammation in elderly patients undergoing laparoscopic gastrectomy. Methods Sixty patients who were of both sexes, American Society of Anesthesiologists Physical Status (ASA-PS) Class I or II, over 65 years of age and undergoing an elective laparoscopic radical gastrectomy were randomly divided into two groups: an oxycodone group (Group O) including 20 males and 10 females and a sufentanil group (Group S) including 21 males and 9 females. The postoperative analgesia regimen was as follows: 40 mg of parecoxib sodium and 0.1 mg/kg of oxycodone was intravenously injected into Group O before the abdomen closure, while 40 mg of parecoxib sodium and 0.1 μg/kg of sufentanil was injected intravenously into Group S. Both groups were infiltrated with 20 ml of 1% ropivacaine at the end of the operation. The level of serum IL-6 and IL-10 were assayed immediately at the following timepoints: at the conclusion of surgery(T1),one hour(T2),six hours(T3) and twenty-four hours(T4) after the completion of the surgery. The numerical rating scale (NRS), the Ramsay sedation score, analgesic-related adverse events, postoperative pulmonary inflammation events and the postoperative stay were recorded. Results Compared with Group S, the serum IL-6 concentrations of Group O decreased at T3 and T4, while the serum IL-10 concentrations increased (P < 0.05). In Group O, the serum IL-6 concentrations at T3 and T4 were lower than those at T1 (P < 0.05). The incidence of postoperative nausea and vomiting（PONV）and pulmonary inflammation in Group O was lower than that in Group S (P < 0.05). At each time point, the NRS of visceral pain in Group O was lower than that in Group S. At six and twenty-four hours after extubation, the NRS of incision pain in Group O was lower than that in Group S (P < 0.05). Conclusion Oxycodone can regulate the level of inflammatory cytokines and reduce postoperative inflammatory response.